2015
DOI: 10.1128/jvi.00121-15
|View full text |Cite
|
Sign up to set email alerts
|

Cellular STAT3 Functions via PCBP2 To Restrain Epstein-Barr Virus Lytic Activation in B Lymphocytes

Abstract: A major hurdle to killing Epstein-Barr virus (EBV)-infected tumor cells using oncolytic therapy is the presence of a substantial fraction of EBV-infected cells that does not support the lytic phase of EBV despite exposure to lytic cycle-promoting agents. To determine the mechanism(s) underlying this refractory state, we developed a strategy to separate lytic from refractory EBV-positive (EBV ؉ ) cells. By examining the cellular transcriptome in separated cells, we previously discovered that high levels of host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 42 publications
2
24
0
Order By: Relevance
“…This study and our earlier studies demonstrate that, in addition to phosphorylation and dimerization of STAT3, modulation of the protein level of STAT3 also regulates its function (22,30,(37)(38)(39). Our data also indicate that STAT3 functions at least partly by repressing the immediate-early gene product RTA, the key latency-to-lytic-phase viral switch.…”
Section: Discussionsupporting
confidence: 59%
“…This study and our earlier studies demonstrate that, in addition to phosphorylation and dimerization of STAT3, modulation of the protein level of STAT3 also regulates its function (22,30,(37)(38)(39). Our data also indicate that STAT3 functions at least partly by repressing the immediate-early gene product RTA, the key latency-to-lytic-phase viral switch.…”
Section: Discussionsupporting
confidence: 59%
“…Activity of the BZLF1 promoter is determined by a balance of positive and negative transcription factors that epigenetically mediate activating and silencing marks on histones. Examples of positive transcription factors include CREB, ATF, AP-1, EBP, ZBP1, and MEF2, while ZEB1, ZEB2, KRAB-ZFPs, KAP1, and STAT3 are negative regulators (5,24,26,(37)(38)(39). If EBV switches into the lytic phase, the switch, i.e., ZEBRA, must remain on for successful production of infectious particles.…”
Section: Discussionmentioning
confidence: 99%
“…They found that various signaling pathways including ATM, p38 and JNKs are activated by ROS and involved in the induction of EBV reactivation in a p53-dependent manner. Also, phosphorylation of the ATF2 transcription factor by p38 and JNKs has been reported to activate Zp 16, implying deregulated ROS signaling might similarly induce EBV reactivation from latency through modification of other redox-sensitive transcription factors that activate Zp and/or Rp, such as early growth response 1 (EGR1) 54,55, Sp1 56, Stat3 57, and c-Jun 58.…”
Section: Host Factors Contributing To the Regulation Of Ebv Reactimentioning
confidence: 99%